DETEKSI KECURANGAN AKADEMIK PADA MAHASISWA D III AKUNTANSI POLITEKNIK HARAPAN BERSAMA TEGAL DENGAN MODELFRAUD TRIANGLE - Widianto, Andri; Sari, Yeni Priatna (Jurnal AKSI (Akuntansi dan Sistem Informasi), 2017)
Higher Education as a national education system has a strategic role in educating the nations life and advancing science and technology by observing and applying the humanities value as well as the sustainable culture and empowerment of the Indonesian nation [1]. The strategic role in educating the life of the nation owned by the higher education is threatened by the fraud practices that occur, and commonly referred to as academic fraud. The data collection techniques used in this study was questionnaires presented in questionnaires; in a form of closed questions made using the interval scale. The T test results showed that the Pressure, Opportunity, Rationalization variables are significant and significant to Academic Fraud while F (simultaneous) F test showed that Pressure, Opportunity, Rationalization variables simultaneously and significantly influence the academic fraud